DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE IN MODERN PUBLIC MANAGEMENT – PERU - Alfaro Castellanos, Eduardo Luis (2023)
From one day to the next everything changed; a “Virus” did it. Nature took a break and we had to walk into the future, but the future made us quickly adapt to it and evolve. The Digital Transformation (DT) showed its true face, technologies are constantly evolving, here is Artificial Intelligence (AI), accompanied by the “cloud”, mobility, Blockchain, Big data analytics, etc., Companies They are constantly improving; Face-to-face banking is yesterday, digital banking is today, they work 365 times around the sun, processing transactions made from a cell phone, with fast, efficient connections, programs that chat with us, and all this to improve and “personalize” their services. achieving loyal and captive clients by “managing risk”. The methodology we have carried out focused on a documentary review of literature with scientific bases such as Scopus, Scielo, among others, that frame the “Modern Public Management of the Peruvian State” who observed the change in their environment and asked ourselves: How complicated is it? What should we do to adapt to DT? Should we work on organizational culture? Give a territorial approach? See the Processes? The Technology? Do we have a DT policy? Can we access financing sources from International Organizations? Since the effects of the pandemic have accelerated all this, we have that “[…] 71.79% of the organizations in Peru are on track in their DT process” (Escudero, 2022, para. 3). The key to the relationship between DT and AI is data management.